Employment policies in the economic restructuring of Latin America and the Caribbean (ILO GenevaCH, 1991)
Reviews the effects of adjustment in the past decade on employment and incomes, in an effort to identify its costs and benefits, as well as the diversity of national situations in the region. Explores the dual dimension of adjustment policies - stablisation and structural adjustment.
Bibliography: p. 71-72